Learning Loss dan Penurunan Kompetensi Literasi dan Numerasi Siswa Sekolah Dasar (SD) di Kecamatan Cikeusik, Kabupaten Pandeglang, Banten - Musoffa Musoffa (Kopertais Wilayah I DKI Jakarta dan Banten, 2022)
Covid 19 has an impact on all aspects of human life, including in the field of education. This, according to several studies, causes a loss of optimal learning opportunities and time (learning loss) which has an impact on the decline in children's competencies, especially literacy and numeracy competencies for elementary school students. This study aims to detect whether learning loss occurs in elementary schools in Cikeusik District, Pandeglang Regency and conduct an assessment of students' literacy and numeracy competencies. The assessment conducted on students from 10 elementary schools in Cikeusik District, Pandeglang Regency showed that literacy and numeracy learning loss for elementary school students in the region was quite significant.